2020
DOI: 10.3389/fmolb.2020.576420
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Microenvironment- Responsive Size-Shrinkable Drug-Delivery Nanosystems for Deepened Penetration Into Tumors

Abstract: Over the years, the manipulation and clinical application of drug-delivery nanosystems for cancer diseases have attracted a rapid growth of academic research interests, and some nanodrugs have been approved for clinic application. Although encouraging achievements have been made, the potency of nanomedicines in cancer treatment is far from satisfaction, and one significant reason is the inefficient penetration of nanoparticles into solid tumors. Particle size is one of the most significant features that influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Notably, the difference in this synthesis was that G CC was formed in a G X reaction solution and G X was not separately attached. As such these multi-dimensional hybrids were self-assembled in situ and each nanocomponent (200 nm and 10 nm) may be used for efficient tumor localization and deep penetration [ 19 , 22 ]. We also found that by changing the amount of glutaraldehyde in the reaction we could tune the size of the satellite nanoparticles ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the difference in this synthesis was that G CC was formed in a G X reaction solution and G X was not separately attached. As such these multi-dimensional hybrids were self-assembled in situ and each nanocomponent (200 nm and 10 nm) may be used for efficient tumor localization and deep penetration [ 19 , 22 ]. We also found that by changing the amount of glutaraldehyde in the reaction we could tune the size of the satellite nanoparticles ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the FDA-approved Doxil and Abraxane, showed only modest therapeutic benefits due to their larger sizes (>100 nm) [ 16 ]. Indeed, several systematic studies concluded that the size of the nanoparticles governs the transport and diffusion within tumor [ 13 , [17] , [18] , [19] , [20] ]. Liang and colleagues evaluated the tumor penetrability of gold nanoparticles of 50 and 100 nm and found that the smaller particles penetrated deeper into the tumor [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that BiF 3 : Ln@PVP NPs have potential as clinical CT contrast agents for tumor and gastrointestinal imaging. However, owing to the limitation of particle size, BiF 3 : Ln@PVP NPs cannot achieve good enhanced permeability and retention (EPR) effect [ 46 ]. The long-term biological safety of BiF 3 : Ln@PVP NPs and the metabolic process in vivo requires further study.…”
Section: Resultsmentioning
confidence: 99%
“…Second, ion competition between hydrogen ions and drug ions that carry the current influenced the drug’s penetration (Cheng et al., 2020 ). When the pH, the concentration of hydrogen ions ([H + ]), increased from 4.81 to 8.10, a significant increase in Q and decreased Flux J ss was observed.…”
Section: Discussionmentioning
confidence: 99%